Think Before They Squeak: Vocalizations of the Squirrel Family - Newar, Sasha L.; Bowman, Jeff (Frontiers in Ecology and Evolution, 2020)
Squirrels are a diverse group in behaviour, morphology, and ecology. This variation is typified by the wide range of vocalizations spanning ground squirrels, tree squirrels, and flying squirrels. Squirrels produce calls that range in frequency, modulation, and function, with a complex set of social calls occurring across the family. We review the history of recording methods used in the description of squirrel vocalization repertoires, with emphasis on how the ecology and methodology impact the vocal ranges reported. The maximum, minimum, and dominant frequencies were considered against popular hypotheses that have attempted to explain the evolution of vocal range in terrestrial mammals. These hypotheses include body size, predator avoidance, sociality, and time partitioning. Phylogenetic generalized least squared modelling revealed that social complexity and open habitats were the strongest drivers of high-frequency communication, whereas body mass constrained the lower frequency limit of vocalizations. Additionally, nocturnality was significantly associated with high-frequency calls, suggesting that flying squirrels, the only nocturnal squirrels, commonly use high-frequency acoustic signals, a finding that merits further investigation. In conclusion, our review provides a unique insight into the role of behavioural ecology on vocal repertoires and the importance of accurate equipment selection for sampling across a diverse taxon.